Faktor – faktor yang berhubungan dengan pemberian ASI eksklusif pada bayi usia 7 – 12 bulan - Eka Trismiyana; Nizomi Satria Winata (Holistik Jurnal Kesehatan, 2020)
Factors associated with exclusive breast-feeding at Pesawaran, Lampung-IndonesiaBackground: Exclusive breastfeeding in Indonesia, especially Lampung Province According to Lampung Health Profile, it is 57.70%, this figure is still far from the provincial target of 80%. For the lowest district of exclusive breast-feeding, there are 49,76% of the total breastfeeding and 32,85% for the Kedondong Pesawaran community health center. From the results of the survey conducted by researchers, the results of 10 mothers 80% of them did not know the benefits of breast-feeding, out of 10 working mothers 70% of them did not give exclusive breast-feeding because they worked as farm laborers, and from 10 mothers 70% of them did not get support from family to give exclusive breastfeeding.Purpose: Knowing the factors associated with exclusive breast-feeding at Pesawaran, Lampung-IndonesiaMethods: The type of quantitative research, the cross sectional approach of the population was  mother who has a baby 7-12 months with a sample number of 225 mothers. Sampling using purposive random sampling and this study uses the questionnaire and analysis of the Chai Square test data.Result: Frequency distribution of respondents ' knowledge is not good 145 respondents (64), good knowledge of the milk is 80 respondents (36) and (p value 0.000 and value Or 14.462). The job distribution of the respondent works or continues to perform day-to-day activities of 177 respondents (78), does not do the job or as Housewives 48 respondents (22) and (p value 0.000 and value Or 6.344). Frequency distribution of family support respondents received support from the 160 respondents family (71), gaining support from the family of 65 respondents (29) and (p value 0.000 and value Or 4.571).Conclusion: The existence of the relationship between knowledge, employment, and the support of the family on the giving of the exclusive breast-feeding Puskesmas Kedodong Regency pesment year 2019. Advised for the Intitusi health services in particular district Puskesmas should more need to improve the knowledge, employment and support of mother's family about the breast-feeding through health workers either in the case or local village midwives with Using other methods such as direct counseling with Nottingham that relate to exclusive breast-feeding, given its important exclusive breast-feeding that is needed by infants 0-6 monthsKeywords: Knowledge; employment; family support; exclusive breast-feedingPendahuluan : Cangkupan ASI eksklusif di Indonesia Khususnya Provinsi Lampung Menurut Profil kesehatan Lampung adalah sebesar 57,70% angka ini masih jauh dari target provinsi sebesar 80%. Untuk kabupaten terendah cangkupan ASI nya Adalah Pesawaran dengan 49,76% dan untuk daerah puskesmas kedondong pesawaran sebesar 32,85%. Dari hasil prasurvey yang dilakukan oleh peneliti didapat hasil dari 10 orang ibu 80% diantaranya tidak mengetahui mamfaat ASI, dari 10 orang ibu bekerja 70% diantaranya tidak memberikan ASI eksklusif karena bekerja sebagai buruh tani, dan dari 10 orang ibu 70% diantaranya tidak mendapat dukungan dari keluarga untuk memberikan ASI eksklusif.Tujuan: Diketahui hubungan faktor pengetahuan, pekerjaan, dukungan keluarga dengan  pemberian ASI eksklusif pada bayi usia 7 – 12 bulan desa Kedondong Kabupaten Pesawaran.Metode: Jenis penelitian kuantitatif, pendekatan cross sectional populASInya seluruh ibu yang memiliki bayi 7-12 bulan dengan jumlah sampel 225 ibu. Penelitian ini mengunakan sampling purpotional random sampling dan penelitian ini mengunakan kuisioner dan analisis data uji Chai Square.Hasil : Distribusi frekuensi pengatahuan responden pengetahuan tidak baik 145 responden (64), pengetahuan baik tentang ASI yaitu 80 responden (36) dan (p value 0.000 dan nilai Or 14,462). Distribusi ferkuensi pekerjaan responden bekerja atau tetap melakukan aktivitas sehari hari 177 responden (78), tidak melakukan pekerjaan atau sebagai ibu rumah tangga 48 responden (22) dan (p value 0.000 dan nilai Or 6,344). Distribusi frekuensi dukungan keluarga responden mendapat dukungan dari keluarga 160 responden (71), mendapatkan dukungan dari keluarga 65 responden (29) dan (p value 0.000 dan nilai OR 4,571).Simpulan: Adanya hubungan antara pengetahuan, pekerjaan, dan dukungan keluarga terhadap pemberian ASI eksklusif diwilayah kerja Puskesmas Kedodong Kabupaten Pesawaran Tahun 2019. disarankan untuk Intitusi pelayanan kesehatan khususnya puskesmas kecamatan harusnya lebih perlu meningkatkan pengetahuan, pekerjaan dan dukungan keluarga ibu tentang ASI melalui petugas kesehatan baik yang ada dipuskes atau bidan desa setempat dengan mengunakan metode lain seperti penyuluhan langsung dengan wokshop yang bekaitan dengan ASI eksklusif , mengingat penting nya ASI eksklusif yang sangat dibutuhkan oleh bayi 0-6 bulan.